Revitalization of South Sulawesi socio-cultural values relating to democracy in the era of regional autonomy - Jumadi Jumadi; Rifai Nur; Patahuddin Patahuddin (Universitas Negeri Yogyakarta, 2016)
This research aims to understand the principles of democracy enforcement in the implementation of regional autonomy, to promote and to revitalize the South Sulawesi socio-cultural values relating to the issue of democracy in the era of regional autonomy, the development of the region potency and the diversity of community to achieve regional and national progress. South Sulawesi since the empire era has posessed socio-cultural values that are closely related to the principles of democracy enforcement. The Socio-cultural values are potential for the regional development, especially in the era of regional autonomy. Social values, one of them are embedded in the democracy principles and foundations in South Sulawesi as the legal basis for organizing the kingdom in South Sulawesi: “rusa’ taro datu, ten rusa’ taro ade’, rusa’ taro ade’ ten rusa’ taro anang, rusa’ anang ten rusa’ taro tomaegae”.means that the decision of datu / king can be canceled by ade ' (council) but the decision of ade' can not be canceled by the king / datu, the decision of ade' can be canceled by public figures, but the willingness of public figures can not be canceled by public figures, the willingness of public figures can be canceled by the society, but the willingness of the society can not be canceled by public figures. This means the highest decision belongs to the society. Keywords: Socio-Cultural Values and Democracy in the era of regional Autonomy.